2009
DOI: 10.1097/gim.0b013e3181b3f42d
|View full text |Cite
|
Sign up to set email alerts
|

Communication, encouragement, and cancer screening in families with and without mutations for hereditary nonpolyposis colorectal cancer: A pilot study

Abstract: Purpose: Known and suspected mutation carriers for hereditary nonpolyposis colorectal cancer are advised to have colonoscopies every 1 to 2 years to detect colorectal cancer. Little is known about colonoscopy completion in families suspected of having hereditary nonpolyposis colorectal cancer but without identified mutations. Methods: This study examined the effect of communication and encouragement on colonoscopy in families with and without known mutations. Twenty-three respondents from 11 families with inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…95 Positive family relationships also predicted increased adherence to recommended screening. 96 Specifically, greater family involvement, communication about risk, and encouragement were associated with a significantly shorter time since last colonoscopy. 96 …”
Section: Hnpccmentioning
confidence: 95%
See 1 more Smart Citation
“…95 Positive family relationships also predicted increased adherence to recommended screening. 96 Specifically, greater family involvement, communication about risk, and encouragement were associated with a significantly shorter time since last colonoscopy. 96 …”
Section: Hnpccmentioning
confidence: 95%
“…96 Specifically, greater family involvement, communication about risk, and encouragement were associated with a significantly shorter time since last colonoscopy. 96 …”
Section: Hnpccmentioning
confidence: 95%
“…Results have highlighted the interpersonal and interdependent nature of responses to genomic information. For example, recent work has indicated that adherence to cancer screening recommendations is associated with the extent to which shared cancer risk is discussed with relatives and, in turn, encouragement to screen is received from relatives (40,50).…”
Section: Cancer Screening Behaviorsmentioning
confidence: 99%
“…Recent work with families affected by hereditary colon cancer has identified a familyencourager communication model: that is, individuals who encourage many family members to seek cancer screening tend to screen themselves; family members who are encouraged by the family encourager also tend to engage in more appropriate screening behaviors (43,50). However, to our knowledge, there is no ongoing research to explore whether these kinship-based processes are taking place with respect to common diseases.…”
Section: Wwwannualreviewsorg • Personalized Genetics and Behavior Cmentioning
confidence: 99%
“…Overall, there were no differences between the groups in the year before receiving test results; however, after receiving test results patients with an inconclusive test were significantly less likely to have endoscopy than mutation-positive patients. Ersig et al (2009b) emphasized that not only mutation status but also familial relationships play an important role. These authors found that time since last screening did not differ according to family mutation status.…”
Section: Hereditary Nonpolyposis Colon Cancermentioning
confidence: 99%